β-Adrenergic agonists differentially regulate highly selective and nonselective epithelial sodium channels to promote alveolar fluid clearance in vivo - Downs, Charles A. (American Physiological Society, 2012)
β-Adrenergic receptors (β-AR) increase epithelial sodium channel (ENaC) activity to promote lung fluid clearance. However, the effect of selective β-AR agonist on highly selective cation (HSC) channels or nonselective cation (NSC) channels in alveolar type 1 (T1) and type 2 (T2) cells is unknown. We hypothesized that stimulation with β(1)-AR agonist (denopamine) or β(2)-AR agonist (terbutaline) would increase HSC and/or NSC channel activity in alveolar epithelial cells. We performed single-channel measurements from T1 and T2 cells accessed from rat lung slices. Terbutaline (20 μM) increased HSC ENaC activity (open probability, NP(o)) in T1 (from 0.96 ± 0.61 to 1.25 ± 0.71, n = 5, P <0.05) and T2 cells (from 0.28 ± 0.14 to 1.0 ± 0.30, n = 8, P = 0.02). Denopamine (20 μM) increased NSC NP(o) in T1 cells (from 0.34 ± 0.09 to 0.63 ± 0.14, n = 7, P = 0.02) and in T2 cells (from 0.47 ± 0.09 to 0.68 ± 0.10, P = 0.004). In vivo X-ray imaging of lung fluid clearance and ICI 118,551 selective inhibition of β(2)-ARs confirmed patch-clamp findings. cAMP concentrations increased following treatment with denopamine or terbutaline (n = 3, P < 0.002). The effects of systemic (intraperitoneal, IP) and local (intratracheal, IT) modes of delivery on lung fluid clearance were assessed. IT delivery of denopamine promoted alveolar flooding, whereas IP delivery promoted delayed fluid clearance. In summary, β-AR agonists differentially regulate HSC and NSC in T1 and T2 cells to promote lung fluid clearance in vivo, and the mode of drug delivery is critical for maximizing β-AR agonist efficacy.